Medicinal Plants Knowledge and Traditional Healing Practices of Mentawai Indigenous People in Indonesia: An Ethnomedicine Approach - Suharmiati Suharmiati; Zulfa Auliyati Agustina; Diyan Effendi (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Medicinal plants have an important role in traditional medicine. Mentawai ethnic in Mentawai islands is one of the indigenous tribes in Indonesia that have strong traditional practices. However, little information is known about the medicinal plants that they use. This study aims to analyze medicinal ingredients used by Mentawai people seen from ethnomedicine and modern pharmacology perspectives. Methods: Data was collected through observations and interviews with key informants in Madobag village, Mentawai Regency, Indonesia. Results: Most of the medicinal plants according to the informant (Sikerei)were used for treating swelling, new wounds, and lymphatic diseases. Based on modern pharmacology literature, some of the plants used by the Mentawai people have the properties of antimicrobial, antiinflammation, and antioxidants. Conclusion: Traditional healer in Mentawai islands has knowledge of medicinal plants even though some of them do not correspond to the modern pharmaceutical science.